2017
DOI: 10.1002/ajmg.b.32536
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental contributions to the association between ADHD and affective problems in early childhood—A Swedish population‐based twin study

Abstract: Few twin studies have explored the relative contribution of genetic and environmental factors to the association between attention deficit hyperactivity disorder (ADHD) and affective problems, and no study has focused on preschool children. We used the classical twin design to explore the genetic and environmental overlap between ADHD symptoms and affective problems in preschool children, based on 879 five-year-old twin pairs born in Sweden 2004Sweden -2005. Questionnaire-based parent-ratings were used to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Family studies that studied the association between ADHD and depression suggest that the cooccurrence is influenced by shared familial factors [54,55]. Twin studies of this issue suggest that shared genetic factors explain the overlap of ADHD with depression, anxiety, and internalizing symptoms [56][57][58][59][60]. For example, Cole et al [59].…”
Section: Psychiatric Comorbiditymentioning
confidence: 99%
“…Family studies that studied the association between ADHD and depression suggest that the cooccurrence is influenced by shared familial factors [54,55]. Twin studies of this issue suggest that shared genetic factors explain the overlap of ADHD with depression, anxiety, and internalizing symptoms [56][57][58][59][60]. For example, Cole et al [59].…”
Section: Psychiatric Comorbiditymentioning
confidence: 99%
“…For example, twin studies find that early-onset-neurodevelopmental disorders share genetic risk with anxiety (Hallett et al 2010 ; Michelini et al 2015 ; Chen et al 2016 ), MDD (Cole et al 2009 ; Lundström et al 2011 ), affective problems (Rydell et al . 2017 ), and OCD (Pinto et al 2016 ). In a study of specific intellectual domains, problems with communication shared a modest degree of genetic risk with adolescent hallucinations and mania (Cederlöf et al 2014 b ).…”
Section: Shared Genetic Risks Across Child- and Adult-onset Disordersmentioning
confidence: 99%
“…31 Secondly, we only included neurodevelopmental and externalizing traits, as both are early onset psychopathology dimensions that are strongly linked to ADHD. Nonetheless, there is also evidence that ADHD in childhood is linked to internalizing traits 28,61 and genomic studies have reported genetic associations across clinical ADHD and depression. 10,43 Future studies assessing genetic specificity and generality in relation to ADHD should therefore aim to also include internalizing traits.…”
Section: Limitationsmentioning
confidence: 99%